2020
DOI: 10.1111/nph.16898
|View full text |Cite
|
Sign up to set email alerts
|

Looking into ‘hair tonics’ for cotton fiber initiation

Abstract: Cotton fiber is the most important source of cellulose for the global textile industry. These hair-like single-celled trichomes develop from ovule epidermis. They are classified into long spinnable lint and short fuzz. A key objective in the cotton industry is to breed elite cultivars with fuzzless seeds carrying high lint yield. Molecular basis underlying lint and fuzz initiation remains obscure. Recent studies indicate fiber initiation is under the control of MYB-bHLH-WDR (MBW) transcription factor complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Motif enrichment analysis of 302 differentially expressed fiber-specific genes revealed a significant enrichment of cis -regulatory motifs belonging to bHLH and C2H2 zinc finger TFs ( Figure 2A ). The TFs that interact with these two motifs are required for different transcriptional regulations at fiber initiation and elongation stages ( Wang L. et al, 2021 ; Wang N. N. et al, 2021 ; Wu et al, 2021 ). However, in At subgenome (142) and Dt subgenome specific (160) DEGs, instead of bHLH, AP2/ERF TF showed significant motif enrichment over the random datasets ( Figures 2A,C ), which was previously reported to control the fiber length ( Mittal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motif enrichment analysis of 302 differentially expressed fiber-specific genes revealed a significant enrichment of cis -regulatory motifs belonging to bHLH and C2H2 zinc finger TFs ( Figure 2A ). The TFs that interact with these two motifs are required for different transcriptional regulations at fiber initiation and elongation stages ( Wang L. et al, 2021 ; Wang N. N. et al, 2021 ; Wu et al, 2021 ). However, in At subgenome (142) and Dt subgenome specific (160) DEGs, instead of bHLH, AP2/ERF TF showed significant motif enrichment over the random datasets ( Figures 2A,C ), which was previously reported to control the fiber length ( Mittal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fate of ovule epidermal cells is committed before and/or on the day of anthesis, which is coordinated by different regulation machinery ( Qin and Zhu, 2011 ; Zhang et al, 2017 ; Prakash et al, 2020 ; Tian and Zhang, 2021 ). Thus, we named this stage as a fiber commitment stage, which ultimately decided the total fiber yield ( Wang L. et al, 2021 ). Cotton fiber yield and its quality are essential agronomical traits, and thereby, significant efforts have been made to understand its biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fiber and Arabidopsis trichome initiation share some similarities but have a different mode of molecular regulation ( Tian and Zhang, 2021 ; Wang et al, 2021a ). Several key genes involved in Arabidopsis trichome initiation have been identified that form a transcriptional network involving three major groups of transcription factors: R2R3-type MYB-basic helix–loop–helix (bHLH)-WD40 repeat (WDR) protein ( Payne et al, 2000 ; Serna and Martin, 2006 ; Grebe, 2012 ; Pattanaik et al, 2014 ; Tian and Zhang, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fibers are single-celled and unbranched trichomes that outgrow from the seed epidermal cells and successively undergo a highly polarized elongation similar to leaf trichomes [ 16 , 17 ]. Therefore, cell fate determination and elongation patterns unveiled from Arabidopsis trichomes may provide a useful framework involved in cotton fiber initiation and elongation.…”
Section: Introductionmentioning
confidence: 99%